Pertumbuhan Musik Metal di Indonesia Akhir 1980-an - Akhmad Syaekhu Rakhman (HEURISTIK: Jurnal Pendidikan Sejarah, 2022)
Research on the growth of metal music in Indonesia in the late 1980s aims to identify the background for the emergence of metal music in Indonesia and to see the enthusiasm of young people for metal music and bring metal music to the Indonesian culture. On the other hand, the method used in this research is a historical research method with 4 stages, namely heuristics, source criticism, interpretation, and historiography. The result of this research is the history of the emergence of metal music in Indonesia, the enthusiasm of young people towards metal music began to emerge in the 1980s. The bond between metal music and Indonesian culture is very opposite to the cultural background of Indonesians who have friendly and polite behavior, are wise, far from aggressive.